Analisis Keterlanjuran Ruang Lingkungan Universitas Muhammdiyah Gorontalo - Jaya, Risman; Rijal, Ahmad Syamsu (UNIVERSITAS NEGERI MAKASSAR, 2021)
Reviewing spatial planning is a must in planning and regional development, besides that, it is also to obtain information related to the suitability of the use of space that has been used. Spatial planning assessment can be based on a tendency towards spatial use and based on land use and spatial function. Techniques and kali have been carried out using spatial analysis with the concept of geographic information systems that cannot be separated from the research parameters used. The method used is a mixed method that combines quantitative and qualitative methods. The quantitative method functions to produce numerical data so that it can be interpreted into a narrative, while qualitative methods are used to describe either numerical data, tables, pictures, or maps into useful narrative information based on the results of the research that has been done. The purpose of this study is to see the progress in the implementation of space suitability in the campus environment of the Muhammadiyah University of Gorontalo. The result of the research shows that the campus area can be classified based on the length of space, which includes the appropriate area in the built area of 1,81537 ha, the undeveloped area of 7,23050 ha and the unsuitable area is in the built area of 0.04513 ha. In addition to producing information related to space suitability, the research results also provide recommendations regarding the plan to use campus space as an alternative for future development.